©G Dear 2010 – Not to be sold/Free to use

Presentation on theme: "©G Dear 2010 – Not to be sold/Free to use"— Presentation transcript:

©G Dear 2010 – Not to be sold/Free to use
Mathematic Extension 1 (Preliminary) Trigonometry Sum & Differences of angles Stage 6 - Year 11 Press Ctrl-A ©G Dear 2010 – Not to be sold/Free to use

Difference of Angles 1 -1 -1 A (cos y, sin y) (cos x, sin x) B 1 x-y x

Differences of Angles x - y We find the sum or difference of angles
to make the hard questions easier. 1 -1 A (cos y, sin y) (cos x, sin x) B 1 x-y x 1 y -1 End of Slide

cos(x – y) = cos x cos y + sin x sin y
Differences of Angles cos(x – y) = cos x cos y + sin x sin y Proof part 1 - distance formula d2 = (x2–x1)2 + (y2–y1)2 AB2 = (cos x – cos y)2 + (sin x – sin y)2 = cos2x – 2 cos x cos y + cos2y + sin2x – 2 sin x sin y + sin2y = (cos2x + sin2x) + (cos2y + sin2y) - 2cos x cos y - 2sin x sin y = 2 - 2(cos x cos y + sin x sin y) 1 Xo-yo End of Slide

cos(x – y) = cos x cos y + sin x sin y
Differences of Angles cos(x – y) = cos x cos y + sin x sin y Proof part 2 – cosine rule a2 = b2 + c2 – 2bc cos A AB2 = – 2(1)(1) cos(x - y) AB2 = 2 – 2 cos(x - y) 2 Xo-yo End of Slide

cos(x – y) = cos x cos y + sin x sin y
Differences of Angles cos(x – y) = cos x cos y + sin x sin y Proof part 3 – from 1 and 2 x x 2 – 2 cos(x-y) = 2 2 - 2(cos x cos y + sin x sin y) 1 x x –2 cos(x-y) = 2 -2(cos x cos y + sin x sin y) 1 cos(x-y) = cos x cos y + sin x sin y xo-yo End of Slide

Sum of Angles 1 -1 A (cos y, sin y) (cos x, sin x) B x+y x y 1 1 -1

Sum & Differences of Angles
xo + yo 1 -1 A (cos y, sin y) (cos x, sin x) B x+y x y 1 1 -1 End of Slide

Sum of Angles cos(x + y) = cos x cos y - sin x sin y Replace y with -y
xo+yo End of Slide

Sum of Angles sin(x + y) = sin x cos y + cos x sin y
Replace x with 90o-x cos(x–y) = cos x cos y + sin x sin y cos((90o-x)– y) = cos(90o-x) cos y + sin(90o-x) sin y cos(90o-(x+y)) = sin x cos y + cos x sin y sin(x+y) = sin x cos y + cos x sin y -1 xo+yo End of Slide

Differences of Angles sin(x - y) = sin x cos y - cos x sin y
Replace y with -y sin (x+y) = sin x cos y + cos x sin y sin (x+(-y)) = sin x cos (-y) + cos x sin (-y) sin (x-y) = sin x cos y + cos x (-sin y) sin(x-y) = sin x cos y - cos x sin y xo-yo End of Slide

Sum of Angles sin(x + y) = sin x cos y + cos x sin y
Replace x with 90o-x cos(x – y) = cos x cos y + sin x sin y cos((90o-x) – y) = cos (90o-x) cos y + sin (90o-x) sin y cos(90o- (x+y)) = sin x cos y + cos x sin y sin(x+y) = sin x cos y + cos x sin y xo+yo End of Slide

Sum of Angles 1 tan x + tan y tan (x+y) = 1 – tan x tan y sin(x+y)
cos(x+y) = sin x cos y + cos x sin y tan(x+y) = cos x cos y - sin x sin y = sin x cos y + cos x sin y cos x cos y = sin x cos y cos x cos y xxxx + cos x sin y cos x cos y xxxx cos x cos y + sin x sin y cos x cos y xxxx xxxx cos x cos y - sin x sin y cos x cos y 1 = tan x + tan y tan(x+y) = 1 - tan x tan y xo+yo End of Slide

Differences of Angles 1 tan x - tan y tan (x-y) = 1 – tan x tan y
sin(x-y) cos(x-y) = sin x cos y - cos x sin y tan(x-y) = cos x cos y + sin x sin y = sin x cos y - cos x sin y cos x cos y = sin x cos y cos x cos y xxxx - cos x sin y cos x cos y xxxx cos x cos y + sin x sin y cos x cos y xxxx xxxx cos x cos y + sin x sin y cos x cos y 1 = tan x - tan y tan(x-y) = 1 + tan x tan y xo-yo End of Slide

Sum & Differences of Angles
cos(x – y) = cos x cos y + sin x sin y cos(x + y) = cos x cos y - sin x sin y sin(x + y) = sin x cos y + cos x sin y sin(x - y) = sin x cos y - cos x sin y tan x + tan y 1 – tan x tan y tan (x+y) = tan x - tan y 1 – tan x tan y tan (x-y) = End of Slide

Similar presentations